Characterization of an Aspergillus niger for Efficient Fatty Acid Ethyl Ester Synthesis in Aqueous Phase and the Molecular Mechanism - Xu, Youqiang; Huang, Huiqin; Lu, Hongyun; Wu, Mengqin; Lin, Mengwei; Zhang, Chunsheng; Zhao, Zhigang; Li, Weiwei; Zhang, Chengnan; Li, Xiuting; Sun, Baoguo (Frontiers in Microbiology, 2022)
Fatty acid ethyl esters are important flavor chemicals in strong-flavor baijiu. Microorganisms are the main contributors to ester synthesis during baijiu manufacture. However, the ester synthesis was unstable between batches. This was owing to a limited knowledge of the mechanisms for ester synthesis by microorganisms. In this work, a fatty acid ethyl ester synthesizing Aspergillus niger strain CGMCC 3.4309 was identified. The conversion ratios of ethyl valerate, ethyl caproate, ethyl caprylate and ethyl caprate were 7.87%, 29.20%, 94.80% and 85.20%, respectively, under the optimized conditions. A comparison of transcriptomes under the initial and optimized ester synthetic conditions indicated 23 genes were up-regulated in transcription level, and encoded enzymes with potential abilities for ester synthesis. Eleven of the enzymes were expressed, and three of them, numbered An605, An1097 and An3131 showed the ability to catalyze fatty acid ethyl ester synthesis under aqueous phase, with capric acid as the preferred substrate. The possible enzymatic catalytic mechanism was proposed based on homology modeling and molecular docking. This study reported for the first time that A. niger showed the ability to efficiently catalyze the synthesis of short and medium chain fatty acid ethyl esters in aqueous phase, identified the key enzymes, and analyzed the basic enzymatic properties. This is helpful to promote the application of related microorganisms and enzyme resources in baijiu industry.